Advanced glycation endproducts and bone quality: practical implications for people with type 2 diabetes. Issue 4 (August 2021) - Moseley, Kendall F.; Du, Zexu; Sacher, Sara E.; Ferguson, Virginia L.; Donnelly, Eve
Abstract : Purpose of review: Individuals with type 2 diabetes (T2D) are at increased risk of fracture, often despite normal bone density. This observation suggests deficits in bone quality in the setting of abnormal glucose homeostasis. The goal of this article is to review recent developments in our understanding of how advanced glycation end products (AGEs) are incorporated into the skeleton with resultant deleterious effects on bone health and structural integrity in patients with T2D. Recent findings: The adverse effects of skeletal AGE accumulation on bone remodeling and the ability of the bone to deform and absorb energy prior to fracture have been demonstrated both at the bench as well as in small human studies; however, questions remain as to how these findings might be better explored in large, population-based investigations. Summary: Hyperglycemia drives systemic, circulating AGE formation with subsequent accumulation in the bone tissue. In those with T2D, studies suggest that AGEs diminish fracture resistance, though larger clinical studies are needed to better define the direct role of longstanding AGE accumulation on bone strength in humans as well as to motivate potential interventions to reverse or disrupt skeletal AGE deposition with the goal of fracture prevention.